Research on the Hydrodynamic Noise Characteristics of a Mixed-Flow Pump - Qiaoyue Yang; Wei Li; Leilei Ji; Weidong Shi; Wei Pu; Yu Long; Xinrui He (Journal of Marine Science and Engineering, 2023)
This study presents a comprehensive investigation of the internal noise characteristics of a mixed-flow pump by combining computational fluid dynamics (CFD) and computational acoustics. The turbulent flow field of the pump is simulated using the unsteady SST k-ω turbulence model in CFD. The contributions of the volute, guide vanes, and impeller to the internal noise are analyzed and compared using the Lighthill theory, FW-H formula, and LMS Virtual Lab software for acoustic simulation. The research findings indicate that the energy of pressure fluctuations in the mixed-flow pump is predominantly concentrated at the blade passing frequency and its low-frequency harmonics. This suggests that the internal noise is mainly in the low-frequency range, with higher energy at the blade passing frequency and its harmonics. Under the 0.6Qdes flow condition, the flow inside the pump becomes more complex, resulting in higher sound pressure levels and sound power levels compared to higher flow conditions. However, for flow conditions ranging from 0.8Qdes to 1.2Qdes, the sound pressure levels gradually increase with increasing flow rate, with the sound pressure level at 1.0Qdes being nearly identical to that at 1.2Qdes. The analysis of sound power level spectra at different flow rates reveals that the distribution characteristics of internal vortex structures directly impact the hydrodynamic noise inside the mixed-flow pump. These research findings provide a significant theoretical basis for noise control in mixed-flow pumps.